(9x-7=4x-8)

Simple and best practice solution for (9x-7=4x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x-7=4x-8) equation:



(9x-7=4x-8)
We move all terms to the left:
(9x-7-(4x-8))=0
We calculate terms in parentheses: +(9x-7-(4x-8)), so:
9x-7-(4x-8)
determiningTheFunctionDomain 9x-(4x-8)-7
We get rid of parentheses
9x-4x+8-7
We add all the numbers together, and all the variables
5x+1
Back to the equation:
+(5x+1)
We get rid of parentheses
5x+1=0
We move all terms containing x to the left, all other terms to the right
5x=-1
x=-1/5
x=-1/5

See similar equations:

| F(x)=3(x)2+6 | | M=3/x | | (3x+16=9x-16) | | 11=355-d | | 5^x=765 | | 1365x-x=0 | | 2(=x+6 | | 3x+9-x=-7 | | 3x²+6x+6=0 | | 14t^2+26t+35=0 | | x+0.23x=0 | | 10x-18=0 | | 3x+9-x=7 | | 7x-1=-5-4x | | −2(k−6)−5=−19 | | (7x+4=5x-16) | | (6x-1)+(2x+15)=18 | | (6x-1)+(2x+15)=4 | | (6x-1)+(2x+15)=27 | | (6x-1)+(2x+15)=17 | | (6x-1)+(2x+15)=23 | | 4y5−1415=y3 | | −2(x+4)=10 | | (8x+15=7x+17) | | 7x-1=5-4x | | x−16=18+3 | | -8h+5h=36 | | (9x+14=3x-2) | | x+18=19+14 | | (3x-2=9x+14) | | (6x+17=8x+9) | | (9x+9=8x+19) |

Equations solver categories